2007
DOI: 10.1111/j.1440-1746.2006.04793.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of malignant ascites in patients with advanced cancer: Peritoneovenous shunt versus paracentesis

Abstract: PVS placement provides an effective treatment option for patients with refractory malignant ascites in advanced cancer, and yields a higher likelihood of discharge compared with conventional paracentesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 15 publications
1
17
0
2
Order By: Relevance
“…• Patients typically need to be closely monitored with a central venous pressure line for 24 hours after PVS placement. • There are 3 common types of shunts: Hyde, Le Veen, and Denver [26].…”
Section: Peritoneovenous Shuntsmentioning
confidence: 99%
“…• Patients typically need to be closely monitored with a central venous pressure line for 24 hours after PVS placement. • There are 3 common types of shunts: Hyde, Le Veen, and Denver [26].…”
Section: Peritoneovenous Shuntsmentioning
confidence: 99%
“…Malignant ascites (MA) is an abnormal accumulation of fluid in the peritoneal cavity as a result of cancer,2 and accounts for ~10% of all cases of ascites. It occurs in many malignancies: adrenal, appendiceal, bladder, breast, cervical, colon, endometrial, esophageal, gall bladder, gastric, liver, lung, lymphoma, melanoma, mesothelioma, neuroendocrine, ovarian, pancreatic, renal, testicular, and thyroid 311. The most common primary site is epithelial ovarian cancer (EOC), accounting for 38% of MA occurring in females 12.…”
Section: Introductionmentioning
confidence: 99%
“…6 Systemic toxicity 5 is shown by the transitory stimulation of the CNS, and the carcinogenic potential of phenol is disputable, according to those authors. 12 Phenol is mainly eliminated by the kidneys, and most of it is excreted in the first 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Hence, various substances have been studied (radioactive colloids, immunostimulators, matrix metalloprotease inhibitors and new chemotherapeutic drugs) with or without hyperthermia, which shows the importance of the development of new methods in order to face the challenge of treating neoplastic ascitis. [1][2][3][4][5][6][7][8][9] A literature review indicated that the infusion of a solution composed of phenol, glycerin, and glacial acetic acid into the prostate of dogs led to reduction in that organ's volume 10 , which resulted from tissue necrosis. The use of the solution was experimentally assayed in Walker's tumor hepatic metastases, leading to suggestive results of necrosis production without alterations in the clinical development of the tumor 11 .…”
Section: Introductionmentioning
confidence: 99%